The Equator Project - Dowey,N; Giles,S; Jackson,C; Williams,R; Fernando,B; Lawrence,A; Raji,M; Barclay,J; Brotherson,L; Childs,E; Houghton,J; Khatwa,A; et al. (2023)
Geography, Earth and Environmental Science (GEES) research will play a vital role in addressing the grand challenges of the 21st century, contributing to many of the UN sustainable development goals and the global energy transition. However, geoscience knowledge cannot be successfully applied to global problems that impact people from all walks of life unless the discipline itself is equitable. There is a well-documented racial and ethnic diversity crisis in GEES subjects in the Global North1 that leads to inequities in who does environmental research. The Equator project set out to increase participation and retention of UK-domiciled Black, Asian and minority ethnic postgraduate research (PGR) students in GEES topics. Our goal was to improve equity and diversity in a research area critical to a more sustainable future; not because of a business case, or for diversity as resource- but for social justice.Equator was a six-month project, funded by the Natural Environment Research Council (NERC), that developed three evidence-based interventions targeting different barriers to racial and ethnic diversity in GEES research. To remove barriers to access, a doctoral training working group was formed to share best practice and develop recommendations to make PhD recruitment more equitable. To improve access and participation, a ring-fenced research school for ethnic minority undergraduate, masters and doctoral students was delivered. To increase retention and improve student experience, a targeted mentoring network pairing students with mentors from both industry and academia was created.Evaluation of interventions took the form of action research with a Theory of Change approach, with surveys used to capture thoughts and reflections in each of the three work packages. This occurred alongside collaborative, self-reflective inquiry within the project team and steering committee. The steering committee included grassroots organisations, higher education institut